Desain Pembelajaran Berbasis Proyek sebagai Strategi Penguatan Berpikir Kritis di Era Digital - Finny Anita; Kurniawati, Tri (IKIP PGRI Pontianak, 2025)
In the digital era, critical thinking skills have become one of the most essential competencies for students. Project-Based Learning (PjBL) has been proven effective in developing these skills. This study aims to provide recommendations for designing project-based learning in course modules to enhance students’ critical thinking skills in the digital era. The research is conducted in five stages: (1) needs analysis; (2) drafting project-based learning materials; (3) integrating design elements into the development of learning materials; (4) involving expert teams in validating the feasibility of the designed materials; and (5) evaluating and refining the developed materials. The study focuses on three courses: (1) Speaking for Academic Purposes, (2) Writing for Academic Purposes, and (3) Methodology in TESOL. The research outcomes include a project-based learning module and a guidebook equipped with instructional materials.